(untitled) (Research, Society and Development, 2022)
Insulin is a hormone responsible for breaking down glucose molecules in the blood and converting them into energy to keep the body in homeostasis. In this way, when it does not work properly, it can cause serious damage to health such as cardiovascular complications, damage to the kidneys and nervous system and in more serious cases it can be fatal. Based on this principle, the most frequent complications triggered by this lack of insulin control are hyperglycemia, hypoglycemia and the Hyperosmolar Hyperglycemic State. These complications are frequent practices present in the professional routine of Emergencies. Therefore, this study is justified by its high social and academic relevance, since diabetes is one of the chronic diseases that most affects the population, causing dysfunctions in the body and culminating in the development of diseases. Therefore, the objective of this research is to show through the scientific literature, which are the most frequent glycemic complications regarding emergency care. The construction of this research proceeded through an integrative literature review, through searches in LILACS and SCIELO databases. Therefore, it is evident that health education practices aim to promote self-care and prepare the return of diabetics, restore and promote health and prevent complications.